PERAN BADAN USAHA MILIK DESA (BUMDES) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI DESA SUGIHWARAS KECAMATAN CANDI KABUPATEN SIDOARJO - Putri, Yohana Stefanie; Arif, Lukman (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to identify the role of BUMDes in increasing the level of community welfare. The method used is descriptive with a qualitative approach. The involvement of village communities in local economic development is an important thing that needs to be continuously pursued and developed. The welfare of village communities is the central goal of all forms of economic activity efforts in the village. Efforts to leverage the rate of village economic growth in line with the recommended trend are through an institution called the Village-Owned Enterprise (BUMDES). Through the role of BUMDES, it is hoped that community welfare can be improved. The results of the study show that BUMDes has a significant role in optimizing existing programs in the village, improving the village economy, empowering village resources and potential. Accompanying the positive findings of the role of BUMDES; it turns out that economic institutions in this village face several obstacles regarding BUMDES management capacity, limited capital, lack of human resource competence, and regulatory support that still needs to be encouraged and strengthened.